Does the size of board of directors and executives affect firm performance in Malaysian listed firms? - Ghasemi, Maziar; Ab Razak, Nazrul Hisyam (EconJournals, 2016)
The worldwide business practices bring more attention to corporate governance. Board of directors is also assumed as the central mechanism of corporate governance. However, whether the board composition will influence firm profitability is still questionable. This paper investigates the effect of the size of board of directors (BOD) and magnitude of executive directors on the firm profitability. Based on GMM regressions on a sample of 267 companies listed on Bursa Malaysia during 2010-2013, it is found that the board size and executive ratio have a positive impact on the firm profitability, although the coefficient value of the executive ratio considerably is greater than the coefficient of the board size. Moreover, persistent profitability is remarked by both models‎. The age of the firm factor has an insignificant relationship with firm profitability. However, leverage has a negative significant influence on the firm profitability, but the effect of liquidity on profitability is positive.